BIOLOGICALLY MEDIATED DISSOLUTION OF GLASS - Staudigel H.; Chastain R.A.; Yayanos A.; Bourcier W. (My University, 1995)
Microbes play an important role in the dissolution of natural and synthetic glasses. The frequent technical use of glass and the abundance of glass at the earth's surface make this process one of the most important weathering reactions. In particular the alteration of volcanic glass provides a direct pathway for mantle-derived materials into the hydrosphere. To begin understanding the kinetics of these processes, we carried out three experiments exposing to seawater polished surfaces of nuclear-waste glass. The durations of experiments were: 410 days with continuously flowing sand-filtered, unsterilized seawater (approx. 2 x 106 l; Exp. 1), 126 days with a marine cyanobacterium culture (50 ml, Exp. 2), and for 225 days under sterile conditions (250 ml, Exp. 3). The sterile experiment (Exp. 3) did not show significant signs of alteration. Exp. 1 resulted in development of a several μm thick biofilm and surface corrosion with grooves exceeding 10 μm in length and 0.5 μm in width. Cyanobacterial cultures also developed a biofilm on the glass surfaces, thinner than in Exp. 1. The glass surfaces themselves were corroded with approximately 0.5-μm-sized pits clustering in 5 μm broad zones parallel to the polishing direction.These experiments show that biofilms develop within months and the corrosion of glass is enhanced by the presence of bacteria. The time scales of biologically mediated glass corrosion are fast when compared to most geological processes. We expect that volcanic ash is rapidly colonized in the oceanic water column, in deep-sea sediments, and in soils. The biological degradation of basaltic glass may contribute significantly to the oceanic nutrient cycle, the chemical exchange between bottom waters and marine sediments, and the fertility of volcanic soils.